Clinical and cardiopulmonary effects of atropine-diazepam-ketamine with and without guaifenesin in calves suffering from acute renal failure - Sarma, B; Kumar, Amresh (The Indian Journal of Animal Sciences, 2012)
Acute renal failure was produced by injecting uranyl nitrate @ 5 mg/kg body weight in 16 crossbred Jersey calves. Atropine sulphate @ 0.04 mg/kg i m - diazepam @ 0.5 mg/kg i v - ketamine @ 5 mg/kg i v; or atropine @ 0.04 mg/kg i m - diazepam @ 0.05 mg/kg I v - (guaifenesin 5% + thiopentone 0.2%) @ 1.5 mg/kg - ketamine @ 5 mg/kg j v were given in 8 animals each respectively. A good anaesthesia with better muscle relaxation was produced in animals given atropine-diazepam (guaifenesin + thiopentone) - ketamine. Significant (P<0.05) increase in heart rate, nonsignificant increase in respiratory rate, minute volume mean arterial blood pressure and decrease in central venous pressure seen after their administration were compensated in 30 to 90 min. ECG did not reveal any marked effect on heart. Both these anaesthetic drug combinations were tolerated well.